Influencing Factors Of Online Advertising Towards Consumer Purchase Intention - Ren, Hongyan (2009)
The present study attempts to explore the relationship between the personal beliefs, namely product information, social image, enjoyment and falsity (no sense) ·and purchase intention, whilest attitude towards online advertising is included as a mediator. Percubaan kajian digunakan untuk meneroka hubungan antara kepercayaan peribadi, maklumat produk, imej sosial, keseronokan, kepalsuan (tanpa perasaan) dan niat pembelian.